JOHN ZONARAS’ TREATISE CONCERNING INADMISSIBILITY OF MARRIAGE OF SECOND COUSINS WITH A SAME WOMAN - A.G. BONDACH (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2007)
n the article commented Russian translation of the family-law Treatise of John Zonarasis offered. The famous canonist proves marriages of persons in sixth degree in-law relationshipto be inadmissible. This treatise continues old tradition of Byzantine law, which expanded listof prohibited degrees little by little